2023
DOI: 10.1177/01626434231170594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video Prompting with Augmented Reality on Functional Living Skills of Students with Intellectual and Developmental Disabilities

Abstract: Training functional living skills is crucial for students with intellectual and developmental disabilities (IDDs) because they are directly related to their independence. The aim of this study was to explore the effect of an augmented reality (AR)–based video prompting (VP) teaching model on the learning of functional living skills among elementary school students with intellectual and developmental disabilities. A multiple-probe, across-subjects, single-case research design was adopted to recruit three partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It can be seen that in terms of in school learning outcomes, students with disabilities have higher absentee and dropout rates, poor academic performance, and lower graduation rates than regular students, but exhibit better in social adaptation and independence [6][7][8][9]24,25]. Wagner et al (2005) analyzed the results of students with disabilities within two years of leaving school and found that 30.6% of students participated in postsecondary education, with most attending two-year community colleges and the least attending four-year universities [23].…”
Section: In-school and Post-school Outcomesmentioning
confidence: 99%
“…It can be seen that in terms of in school learning outcomes, students with disabilities have higher absentee and dropout rates, poor academic performance, and lower graduation rates than regular students, but exhibit better in social adaptation and independence [6][7][8][9]24,25]. Wagner et al (2005) analyzed the results of students with disabilities within two years of leaving school and found that 30.6% of students participated in postsecondary education, with most attending two-year community colleges and the least attending four-year universities [23].…”
Section: In-school and Post-school Outcomesmentioning
confidence: 99%